Anti-epidermal growth factor receptor skin toxicity: a matter of topical hydration. Issue 2 (February 2016) - Ferrari, Daris; Codecà, Carla; Bocci, Barbara; Crepaldi, Francesca; Violati, Martina; Viale, Giulia; Careri, Carmela; Caldiera, Sarah; Bordin, Veronica; Luciani, Andrea; Zonato, Sabrina; Cassinelli, Gabriela; et al.
Abstract : Skin toxicity is a frequent complication of anti-epidermal growth factor receptor therapy, which can be an obstacle in maintaining the dose intensity and may negatively impact on the clinical outcome of cancer patients. Skin lesions depend on the disruption of the keratinocyte development pathways and no treatment is clearly effective in resolving the cutaneous alterations frequently found during anti-epidermal growth factor receptor therapy. Among systemic treatments, oral tetracycline proved to be useful in preventing skin manifestations. We describe the case of a patient affected by metastatic colorectal cancer, for whom a combination of chemotherapy and cetuximab was used as second-line treatment. The patient developed a symptomatic papulopustular skin rash that disappeared completely after a twice-daily application of a hydrating and moisturizing cream, mainly consisting of a mixture of paraffin, silicone compounds, and macrogol. The marked cutaneous amelioration allowed the patient to continue cetuximab without any further symptoms and was associated with a partial radiological response.